Pembangunan Sistem Informasi Manajemen Akademik Sekolah Dasar (Studi Pada SDN Wates Kabupaten Kediri) - Jawara Wahyu Al Faraday; Satrio Agung Wicaksono; Mochammad Chandra Saputra (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
School as a formal educational institution which is a place to seek knowledge, in teaching and learning activities. The national education system in Indonesia is also regulated in Law No. 20, which states that basic education is a basic prerequisite for higher education. SDN Wates is a public elementary school located in Wates District Kediri District. However, there are several things such as the dissemination of manually-made information, the process of registration and refinement of data that is still done manually, the process for the old students to see all the value of the subjects, and also the data collection of alumni is also difficult. Therefore the need for information systems that can help deal with the problem. The process of enrollment and filling of students, as well as filling in the score can be simplified by using the Management Information System of the Primary School of Wates Kediri Regency built with agile method and implemented on the website, after the result of the User acceptance test given to the parents of the applicant students (the percentage of UAT by 85%), and the teacher student selection (UAT percentage score of 80%), as well as the teacher as a student appraiser (UAT percentage value of 90%)